Conception and Responsibility of Local Government on Mining in East Tulabolo Village - Dolot Alhasni Bakung; Zainal Abdul Aziz Hadju; Sri Nanang Meiske Kamba (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2022)
Utilizing Natural Resources is indeed an interesting phenomenon, and this activity can benefit the parties involve, from local people’s elements, companies, and government. However, in practice, the parties that carry out mining activities sometimes do not meet the applicable rules and do not get permission from the local government. This study aims to determine the conception of the regulation of the use of Natural Resources in the form of mining in the National Law and the extent of responsibility of local governments in regulating the mining of the people in the village of East Tulabolo. This study uses empirical juridical research methods. Using interview techniques and samples in this study amounted to 4 respondents. The results of this study indicate that the use of Natural Resources in the form of mining in the legal conception must obtain permission from the local government to be carried out based on Mining Permit (IUP), People’s Mining Permit (IPR or IUPK) and for the responsibility carried out by the local government has not been maximized because of the eight mining sites only 1 location in order by the local government.